PENGEMBANGAN MEDIA INTERAKTIF PADA MATA PELAJARAN IPS EKONOMI BERDASARKAN MOTIF DAN PRINSIP EKONOMI DI SMPN 3 SIDOARJO - Kirwani, ; Emma Widyasari, (Pendidikan Ekonomi, 2010)
The research was to find out the process of interactive CD media development its effectiveness to enhance learning results. The study was a developmental research and classroom action research. The subjects of the study were experts in media, learning material experts, and eight graders of classroom 1 and seven graders of classroom in 4 SMP Negeri 3 Sidoarjo. The results of the research indicated that the media development  generated interactive CD learning media. In addition, the classical mastery of learning objectives increased, that is, 85.71 %, 88.7 %, and 97 % respectively. Students also responded positively to the use  of interactive CD as learning media.